The Naqshbandiyah Order in the Perspective of Scientific Studies: A Systematic Literature Review - Syamsidar, Cut; Syawaluddin (Analisis: Jurnal Studi Keislaman, 2026)
The Naqshbandiyah Sufism is a Sufi tradition that has a significant influence on the spiritual, educational, and social life of Muslim communities. However, the development of scientific studies on the Naqshbandiyah Sufism remains scattered, partial, and has not been systematically synthesized. This study aims to map the direction of study development, dominant themes, methodological approaches, and research gaps in the study of the Naqshbandiyah Sufism. This study uses a Systematic Literature Review (SLR) approach with reference to the PRISMA framework through the stages of identification, screening, eligibility assessment, and inclusion of articles. Data were obtained from scientific journal articles for the period 2020–2025 through Google Scholar and the Directory of Open Access Journals (DOAJ). From the selection process, five articles were obtained that met the inclusion criteria and were analyzed using thematic synthesis. The research findings indicate five main theme clusters: spirituality, education, social, values, and the dynamics and development of the Sufism. This research contributes to strengthening the study of Sufism and contemporary Islamic studies through directed conceptual mapping and offers a further research agenda that is more interdisciplinary, comparative, and responsive to changes in modern Muslim society.